The Daily Erosion Project – daily estimates of water runoff, soil detachment, and erosion. Issue 5 (22nd December 2017) - Gelder, Brian; Sklenar, Tim; James, David; Herzmann, Daryl; Cruse, Richard; Gesch, Karl; Laflen, John
Abstract: Water runoff and sediment transport from agricultural uplands are substantial threats to water quality and sustained crop production. To improve soil and water resources, farmers, conservationists, and policy‐makers must understand how landforms, soil types, farming practices, and rainfall interact with water runoff and soil erosion processes. To that end, the Iowa Daily Erosion Project (IDEP) was designed and implemented in 2003 to inventory these factors across Iowa in the United States. IDEP utilized the Water Erosion Prediction Project (WEPP) soil erosion model along with radar‐derived precipitation data and government‐provided slope, soil, and management information to produce daily estimates of soil erosion and runoff at the township scale (93 km 2 [36 mi 2 ]). Improved national databases and evolving remote sensing technology now permit the derivation of slope, soil, and field‐level management inputs for WEPP. These remotely sensed parameters, along with more detailed meteorological data, now drive daily WEPP hillslope soil erosion and water runoff estimates at the small watershed scale, approximately 90 km 2 (35 mi 2 ), across sections of multiple Midwest states. The revisions constitute a substantial improvement as more realistic field conditions are reflected, more detailed weather data are utilized, hill slope sampling density is an order of magnitude greater, and results are aggregated based on surface hydrology enabling further watershed research and analysis. Considering these improvements and the expansion of the project beyond Iowa it was renamed the Daily Erosion Project (DEP). Statistical and comparative evaluations of soil erosion simulations indicate that the sampling density is adequate and the results are defendable. The modeling framework developed is readily adaptable to other regions given suitable inputs. © 2017 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd. Abstract : A process based water erosion estimation model, WEPP, is supported by inputs sourced via remote sensing technologies and existing soil geographic databases to yield hill slope sheet and rill erosion estimates across large areas of the Central US. This system can be applied to other regions as well depending on input availability, but output resolution and potential accuracy will depend on input quality and resolution. Erosion rates are currently reported daily at the HUC12 watershed (40‐160 square kilometer) spatial resolution.